2002
DOI: 10.1128/aac.46.5.1425-1434.2002
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Assessment of Clarithromycin in a Murine Model of Pneumococcal Pneumonia

Abstract: The pharmacodynamic profile of clarithromycin (CLR) was evaluated with a murine model of pneumonia. Eight Streptococcus pneumoniae isolates, including three macrolide-sensitive and five macrolide-resistant strains, were inoculated intratracheally into immunocompromised ICR mice as 10 8 -CFU bacterial suspensions. Orally administered CLR daily doses ranging from 5 to 600 mg/kg of body weight were given over 5 days, during which animal survival was monitored. The bacterial density in lung tissues was examined af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
64
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 22 publications
3
64
0
Order By: Relevance
“…2 ml of diluent, twice daily for 21 days. A previous study showed that this regimen provides human-simulated exposures in the murine pneumonia model for the parent compound CLR (Tessier et al, 2002). For administration per os, special feeding cannulas were used with small ball tips, and then cleaned and sterilized in self-sealing pouches.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 ml of diluent, twice daily for 21 days. A previous study showed that this regimen provides human-simulated exposures in the murine pneumonia model for the parent compound CLR (Tessier et al, 2002). For administration per os, special feeding cannulas were used with small ball tips, and then cleaned and sterilized in self-sealing pouches.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma samples were stored frozen at À70 8C until assayed using a validated HPLC methodology at the Center for Anti-Infective Research and Development, Hartford Hospital (Tessier et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…All isolates were maintained in skim milk medium (BD Biosciences, Sparks, Md.) at Ϫ80°C and subcultured twice on trypticase soy agar with 5% sheep blood (BD Biosciences) before use in in vitro and in vivo experiments [8]. MICs of NCEs and rifampin were determined against S. pneumoniae strains SPN 21, SPN 95, and SPN 100 in triplicate using standard CLSI (previously NCCLS) methods [11].…”
mentioning
confidence: 99%
“…Mice were rendered neutropenic by IP injection of cyclophosphamide (Cytoxan; Bristol-Myers Squibb, Princeton, N.J.) 150 mg/kg at four days and 100 mg/kg at 1 day prior to inoculation [13,14]. Pneumonia was induced via oropharyngeal inoculation of a 0.05 ml suspension of SPN 100 prepared from an inoculum adjusted to approximately 10 8 CFU/ml as described previously [8]. By 8 to 16 hours post inoculation, all animals showed signs of infection including rough coat appearance and limited mobility.…”
mentioning
confidence: 99%
See 1 more Smart Citation